Studi In-Vivo Potensi Ekstrak Daun Akway (Drimys cf. piperita) Sebagai Antihiperglikemia - Risanyel Elsan Tuturop; A. M. Muslihin; Lukman Hardia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background : Hyperglycemia is a metabolic condition characterized by an increase in blood glucose levels above normal limits and is the main characteristic of diabetes mellitus, a chronic disease with a prevalence that continues to increase in various countries. The akway plant (Drimys cf piperita.) is endemic to the Sorong Mountains, Southwest Papua . Its leaves are known to contain various bioactive compounds such as flavonoids, tannins, saponins, and alkaloids. Purpose: This study aims to test the ability of akway leaf extract to lower blood sugar levels in vivo in white mice that were previously raised glucose levels through glucose solution. Method : This study design is an experimental laboratory with five treatment groups, namely negative control (Na-CMC 0.5 mg), positive control (glibenclamide 3 mg), and three groups of akway leaf extracts, each at doses of 100, 200, and 400 mg/kg BW. Hyperglycemia was induced for 7 days using a glucose solution. Blood glucose measurements were performed at 30, 60, 90, 120, and 150 minutes using a glucometer. Data analysis used One-Way ANOVA followed by a post -LSD test. Results: Akway leaf extract at a dose of 200 mg/kg BW provided the highest reduction in blood glucose, namely 54.24%, which was statistically significant (<0.05) and even better than glibenclamide (51.15%). Meanwhile, a dose of 400 mg/kBW actually produced lower effectiveness (45.85%). Implications: Akway leaf extract has been proven to have antihyperglycemic activity with an optimal dose of 200 mg/kgBW.